2003
DOI: 10.1080/13614530410001692013
|View full text |Cite
|
Sign up to set email alerts
|

Managing change and embedding innovation in academic libraries and information services

Abstract: The paper examines the management of change and the embedding of innovation in academic libraries and information services during a period of considerable and continuous change. Detailed examples are given from the author's own institution that adopts a very structured and corporate approach to strategic planning. The internal and external factors driving organisational change in the UK Higher Education (HE) sector are identified using a PEST (Political, Economic, Social, Technological) analysis, and a detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…More specifically, open communication OS influences strategy through team-based OS, suggesting that an organisational structure that allows open communication – not only among employees but also between employees and managers – and encourages team working plays a pivotal role in knowledge strategy implementation success. Flatter structures and team working, being more flexible, are generally considered more appropriate in times of change (Atkinson, 2003; Maponya, 2004; Moran, 2001). IT, on the other hand, has a weak positive influence on strategy via open communication OS.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, open communication OS influences strategy through team-based OS, suggesting that an organisational structure that allows open communication – not only among employees but also between employees and managers – and encourages team working plays a pivotal role in knowledge strategy implementation success. Flatter structures and team working, being more flexible, are generally considered more appropriate in times of change (Atkinson, 2003; Maponya, 2004; Moran, 2001). IT, on the other hand, has a weak positive influence on strategy via open communication OS.…”
Section: Discussionmentioning
confidence: 99%
“…Atkinson (2003) reviewed the process of SWOT analysis at the Learning Resources Centre of the University of Glamorgan (UK). This review revealed that issues that were identified in the process could be grouped around the following factors: human resources; building and equipment; financial; management; and products and services.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…This review revealed that issues that were identified in the process could be grouped around the following factors: human resources; building and equipment; financial; management; and products and services. Atkinson (2003, p. 31) argues that these factors are “relevant to all higher education library and information services but will vary from institution to institution as to whether they are strengths, weaknesses, opportunities or threats”. Consistent with these findings, the present study concluded that the strengths, weaknesses, opportunities, and threats of each of the academic libraries in Oman fall in one or more of the following issues: human resources; financial resources; management and leadership; products and services; building and space; library location; facilities and equipment; and cooperation and communication (see Table II).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For libraries, library managers have had concerns about finding new approaches to library operations a long time ago; for example, Rau (2007) discusses three examples from 1960s to 1970s that included use of Poisson modelling, queuing theory, Monte Carlo and other simulation techniques. As for investigating library processes, Atkinson (2003) used PEST analysis (which is a high level strategic analysis) to deal effectively with a change in strategic framework. PEST analysis helps illustrating the complex environment where academic libraries and information services reside and operate, by listing the political, economic, social and technological factors which affect the services provided.…”
Section: Business Process Modelling In Academic Librariesmentioning
confidence: 99%